Abnormal real activities, meeting earnings targets and firms' future operating performance: evidence from an emerging economy. Issue 2 (12th August 2021) - Alhaddad, Lara M.; Whittington, Mark; Gerged, Ali Meftah
Abstract : Purpose: This paper aims to examine the extent to which real earnings management (REM) is used in Jordan to meet zero or previous year's earnings, and how this impacts the subsequent operating performance of Jordanian firms. Design/methodology/approach: The study used a sample of 98 Jordanian listed firms over the 2010–2018 period. To test the research hypotheses, which are formulated in accordance with both, agency theory and signalling theory, multivariate regression is performed using a pooled OLS estimation. Additionally, a two-step dynamic generalised method of moment (GMM) model has been estimated to address any concerns regarding the potential occurrence of endogeneity issues. Findings: The results show that Jordanian firms that meet zero or last year's earnings tend to exhibit evidence of real activities manipulations. More specifically, suspect firms show unusually low abnormal discretionary expenses and unusually high abnormal production costs. Further, consistent with the signalling earnings management argument, the authors find that abnormal real-based activities intended to meet zero earnings or previous year's earnings potentially improve the subsequent operating performance of Jordanian firms. This implies that REM is not totally opportunistic, but it can be used to enhance the subsequent operating performance of Jordanian firms. Our findings are robust to alternative proxies and endogeneity concerns. Practical implications: The findings have several implications for policymakers, regulators, audit professionals and investors in their attempts to constrain REM practices to enhance financial reporting quality in Jordan. Managing earnings by reducing discretionary expenses appeared to be the most convenient way to manipulate earnings in Jordan. It provides flexibility in terms of time and the amount of spending. The empirical evidence, therefore, reiterates the crucial necessity to refocus the efforts of internal and external auditors on limiting this type of manipulation to reduce the occurrence of REM activities and enhance the subsequent operating performance of listed firms in Jordan. Drawing on Al-Haddad and Whittington (2019), the evidence also urges regulators and standards setters to develop a more effective enforcement mechanism for corporate governance provisions in Jordan to minimise the likelihood of REM incidence. Originality/value: This study contributes to the body of the accounting literature by providing the first empirical evidence in the Middle East region overall on the use of REM to meet zero or previous year earnings by Jordanian firms. Moreover, the study is the first to empirically examine the relationship between REM and Jordanian firms' future operating performance.